2015
DOI: 10.1074/mcp.m115.052894
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Network of the Gap Junction (GJ) Protein Connexin43 (Cx43) is Modulated by Ischemia and Reperfusion in the Heart*

Abstract: The coordinated and synchronized cardiac muscle contraction relies on an efficient gap junction-mediated intercellular communication (GJIC) between cardiomyocytes, which involves the rapid anisotropic impulse propagation through connexin (Cx)-containing channels, namely of Cx43, the most abundant Cx in the heart. Expectedly, disturbing mechanisms that affect channel activity, localization and turnover of Cx43 have been implicated in several cardiomyopathies, such as myocardial ischemia. Besides gap junction-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
1
55
0
Order By: Relevance
“…However, it remains to be determined whether this is a direct or indirect interaction in most cases. [67][68][69] Such interaction studies have mostly focussed on Cx43 as it is nearly ubiquitously expressed. In the rat heart, mass spectrometry allowed identification of more than 400 proteins interacting with Cx43.…”
Section: Interactions With Other Proteinsmentioning
confidence: 99%
“…However, it remains to be determined whether this is a direct or indirect interaction in most cases. [67][68][69] Such interaction studies have mostly focussed on Cx43 as it is nearly ubiquitously expressed. In the rat heart, mass spectrometry allowed identification of more than 400 proteins interacting with Cx43.…”
Section: Interactions With Other Proteinsmentioning
confidence: 99%
“…An apparent increase of intercalated Cx43 may be considered as a tendency for cardiac recovery. Martins‐Marques et al have demonstrated that ischemic conditions in the heart impact far‐ranging aspects of Cx43 biology such as its interactome . We also probed Cx43 localization in the aforementioned set of four, patient‐matched, cases of non‐ischemic (dilated) cardiomyopathy (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…The reason was probably due to the interaction of Gja1 with these proteins involved in gene transcription. Indeed, accumulating data have identified a lot of Gja1-interacting partners (Butkevich et al 2004, Singh et al 2005, Dai et al 2007, Martins-Marques et al 2015. However, the regulatory mechanisms of Gja1 on the expression of Ccnd3, Cdk4 and Hand2 in uterine stromal cells remain to be determined.…”
Section: :2mentioning
confidence: 99%